Using AI in the creation of municipality slogans - Hakala, Ulla (Springer Nature, 2025)
In this exploratory study, Chat Generative Pre-trained Transformer (ChatGPT), a chatbot developed by OpenAI, is utilized in the creation of slogans for Finnish municipalities in their place-branding eforts. The purpose is to investigate whether ChatGPT could provide the basis for a constructive slogan invention process for a city. Ideally, by adopting ChatGPT into their branding eforts, municipalities could save time and money. The issue is empirically explored in two phases: the frst utilizes ChatGPT in the creation of slogans for the 20 largest municipalities in Finland. The second introduces an expert human perspective on the matter by interviewing representatives of three major Finnish cities to garner their thoughts on the use of AI in place branding and on AI-generated slogans.Place branding is more complex than mere promotional elements (Govers in Place Brand Public Diplomacy 9:71–75, 2013), yet, slogans are being widely used by municipalities as traditionally also by companies.